Genetic Polymorphism of β-Casein Gene in Gir and Mulki cattle of Narmadapuram Division of Madhya Pradesh State - Barwar, Rohit; Thakur, Mohan Singh; Joshi, Shrikant; Khan, Asad (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
This study was aimed to investigate the genetic polymorphism of β-casein) gene in 75 cattle (Gir=35 and Mulki=40) of Narmadapuram division of Madhya Pradesh State. Genomic DNA was extracted from white blood cells of each cattle as per the standard laboratory techniques. The concentration of DNA in isolate of each sample was found within the range of 174.90 ng/µL to 3678.80 ng/ µL. PCR product of 251 bp size was obtained by amplification of DNA samples for exon-7 of β-casein gene. The PCR-RFLP analysis of amplicons of β-casein gene revealed the distribution of only one genotype (A2A2) in both Gir and Mulki cattle. Frequency of A2 allele was found to be maximum in the population. The results of these studies have shown that the A2 allele is more abundant in populations of Gir and Mulki cattle in Narmadapuram divsion.
Keywords: Beta casein; Cattle; Genetic; Gir; Mulki; Polymorphism